Bioactive, antioxidant, industrial, and nutraceutical applications of banana peel - Maligi Bhavani; Sonia Morya; Deepika Saxena; Chinaza Godswill Awuchi (International Journal of Food Properties)
People usually waste or discard the numerous benefits of banana peel due to a lack of awareness. Banana peel is a rich source of many bioactive compounds like carotenoids, biogenic amines, polyphenols, phytosterols, and antioxidants. It also contains minerals like iron, calcium, sodium, phosphorus, magnesium, and good levels of dietary fiber. The use of antioxidants present in banana peels can help reduce the risk of diseases like cancer. Antioxidants play a crucial role in the removal of toxins from the human body. One complete banana comprises about 30–40% peel, and the rest is the pulp portion. Banana peels are used in a wide range of industries like cosmetics, medicine, food processing, beverages, textiles, energy resources, paper manufacture, bio-absorbents, biofuel production, and the agricultural sector. An epic transformation in different industrial sectors can be seen because of the versatile nature of banana peel. In agricultural sectors, banana peel can be used as fertilizer to enhance the soil's physical properties, crop quality, and yield due to potassium. Even fiber-rich banana peels can be used to treat constipation problems. Banana peel carries anti-inflammatory properties that can be used in daily life as a first-aid at home to control, reduce, and cure inflammation and infections. Banana is commonly available in our homes, and thus it can be known as a zero-budget organic cosmetic product. Industrial products like paper, fiber, and textiles can be manufactured from banana peels.